Asymmetries in paddle force influence choice of stroke type for canoe slalom athletes - Wakeling, James M.; Smiešková, Stanislava; Pratt, Jaylene S.; Vajda, Matej; Busta, Jan (Frontiers in Physiology, 2023)
Canoe slalom is an Olympic discipline where athletes race down a whitewater course in kayaks (K1) or canoes (C1) navigating a set of down-stream and up-stream gates. Kayak paddles are symmetrical and have a blade at each end, whereas C1 paddles have only one blade that must be moved across the boat to perform strokes on either the right or left side. Asymmetries in paddle force between the two sides of the boat may lead to a reduction in predicted race time. The purpose of this study was to quantify asymmetries in the paddle forces between the two sides for slalom paddling. Paddle forces for 42 canoe slalom athletes (C1 and K1) were quantified from the straight sections of a flat-water figure-of-eight course. Paddle forces were measured using strain gauges embedded in the paddle shaft, stroke type was identified using video, and boat trajectory was tracked using inertial measurement units and high-speed GPS: data were fused using in-house analysis software. Paddle forces were quantified by their peak force, and impulse during the stroke. Paddle forces for the kayakers had asymmetries of 14.2 to 17.1 % for the male K1M and 11.1 to 14.4 for the women K1W. Canoeists were no more asymmetrical than the kayakers for their 'on-side' strokes between the right and left sides.However, there were considerable differences for their 'off-side' strokes: male C1M off-side paddle forces were similar to their 'on-side' forces for the same side, but the women C1W had a significantly lower (-20.8 to -29.5 %) paddle forces for their 'off-side' strokes compared to their 'on-side' strokes on that same side. Despite an increasing number of younger male athletes being introduced to the switching technique, and it being used by C1M athletes in international competitions since 2014, C1M paddlers still do not use switching transitions as much as C1W. The data from this study indicate that there is a biomechanical reason for this